Effect of Isothermal Annealing on Microstructural Morphology of Martensite in a Super Martensitic Stainless Steel subjected to different prior conditions - Jasdeep (My University, 2013)
A ternary Fe–Cr–Ni super martensitic stainless steel alloy has been investigated during isothermal annealing after subjecting it to different prior conditions. The difference in morphology has been observed for the deformed and annealed martensite after isothermal annealing. The as-received hot rolled plate of martensitic microstructure was cold rolled to 80% thickness reduction. The phase transformation studies by X-ray diffraction analysis of hot and cold rolled specimens showed presence of retained austenite in air cooled as well as in water quenched state after solution annealing/austenizing temperature of 1060°C; showing austenite retention at room temperature, thus justifying its composition. Critical temperatures (As, Af and Ms) were established from empirical relations and were validated with literature. Isothermal annealing was carried out on cold rolled and cold rolled annealed samples between As and Af for different time periods ranging from 1 min to 2.5 min. The recrystallisation behaviour and microstructural morphology changes in cold rolled and cold rolled annealed material was studied in detail by Electron Back Scatter Diffraction (EBSD), and further supported by X-ray Diffraction analysis and hardness values measured by Vickers’s hardness. The morphology of martensite changed entirely from lath martensite to equiaxed grains in cold rolled samples while cold rolled annealed samples showed both morphologies (i.e. equiaxed and typical martensitic lath) at certain isothermal annealing temperatures. The tensile properties of the cold rolled and the cold rolled isothermally annealed samples were evaluated and compared. The cold rolled isothermally annealed samples provided a good combination of strength and ductility at the selected heat treatment parameters.
Keywords: SMSS; Isothermal Annealing